Association between socioeconomic status and the prevalence of intestinal worm infection in primary school children - Sri Alemina Ginting; Isra Firmansyah; Dedi Satria Putra; Dachrul Aldy; Syahril Pasaribu; Chairuddin P Lubis (Paediatrica Indonesiana, 2004)
Background In Indonesia, medical problems are indicated bydiseases associated with low socioeconomic status. The preva-lence of intestinal worm is still high in Indonesia.Objective The purpose of this study was to find the associationbetween socioeconomic status and the prevalence of intestinalworm infection.Methods A cross sectional study was done on 120 primary schoolchildren in Suka Village, Karo District, North Sumatra Province.Subjects were selected by means of random sampling. Kato Katzmethod was used in stool examination. Socioeconomic status wasreferred from the Survey Keluarga Sejahtera (Wealth Family Sur-vey) 1998 by the BKKBN (the National Coordination Board onFamily Planning). Data of socioeconomic status were collected byinterview using a questionnaire and analyzed by chi square test; pvalue of <0.05 was considered to be statistically significant.Results Eighty-four subjects (70%) suffered from intestinal worminfection. There was no significant association between either age(p=0.811) or nutritional status (p=0.792) and intestinal worm infec-tion, but there was significant association between sex and intes-tinal worm infection (p=0.028). There was also association betweenintestinal worm infection and father’s education (p=0.044). Mother’soccupation had a significant association with intestinal worm in-fection (p=0.001), but father’s occupation (p=0.474) did not. Nei-ther parents’ income (p=0.429) nor socioeconomic status (p=0.098)was associated with intestinal worm infection.Conclusion There was significant association between intestinalworm infection and sex, father’s education or mother’s occupation